2013
DOI: 10.17705/1thci.00057
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Psychographic Beliefs on Website Usability Requirements

Abstract: Designing websites that are responsive to customer needs is a critical prerequisite for the success of online services. To date, much research has focused on understanding which design requirements can be successfully applied to a website's design. However, there has been limited research examining why some requirements may have more or less importance to customers. In addition to demographic characteristics, we propose that psychographic characteristics influence usability-related requirements. To develop our… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 81 publications
0
7
0
Order By: Relevance
“…For example, Hur et al (2017) revealed generational differences in TR effects by comparing millennial and mature consumers. Massey et al (2013) found that people's prior Web experience attenuates the influence of TR on a website's perceived usability. Regarding situational moderators, Lam et al (2008) showed that the negative effect of one TR dimension, insecurity about Internet use, is stronger in high-risk usage situations.…”
Section: Moderators In Technology Readiness Researchmentioning
confidence: 94%
See 2 more Smart Citations
“…For example, Hur et al (2017) revealed generational differences in TR effects by comparing millennial and mature consumers. Massey et al (2013) found that people's prior Web experience attenuates the influence of TR on a website's perceived usability. Regarding situational moderators, Lam et al (2008) showed that the negative effect of one TR dimension, insecurity about Internet use, is stronger in high-risk usage situations.…”
Section: Moderators In Technology Readiness Researchmentioning
confidence: 94%
“…We therefore classify technologies depending on whether they provide hedonic (e.g., augmented reality fashion application) or utilitarian (e.g., Internet banking) services. While hedonic technologies are pleasure-oriented, utilitarian technologies are productivity-oriented (Massey et al 2013). We expect that the TR motivators have a stronger influence on technology perception and use for hedonic technologies, whereas TR inhibitors display a stronger effect for utilitarian technologies.…”
Section: Moderating Role Of Hedonic Versus Utilitarian Technologiesmentioning
confidence: 96%
See 1 more Smart Citation
“…Individuals with high discomfort traits would consider technology as more complex. They believe that technology is too complicated and was not designed to be used by normal people (Massey et al, 2013). As such, they perceive technology as something that is not easy to use (Walczuch et al, 2007).…”
Section: Inhibitors Of Tr -Discomfort and Insecuritymentioning
confidence: 99%
“…It should be noted that utilitarian and hedonic consumption has been extensively researched in marketing since the early 1990s (Babin et al, 1994) and also more recently in the field of technology (Blut et al, 2016). Utilitarian technologies are those that enhance productivity, whereas hedonic technologies are pleasure-orientated (Massey et al, 2013). Mobile guided tour apps are pleasure-orientated tools, but the motivating and inhibiting factors for adoption can relate to performance (especially for tour guides) which is more utilitarian than hedonic.…”
Section: Introductionmentioning
confidence: 99%